Strategi Survival Dalam Mempertahankan Eksistensi Warung Sate Blendet Di Balong Kabupaten Ponorogo - Elsy Rozim Pratiwi; Ajeng Wahyuni (Niqosiya: Journal of Economics and Business Research, 2023)
This research aims to identify and analyze the constraints of Sate Blendet traders in running a business, the survival strategy used by Sate Blendet traders to maintain their existence, and the results of implementing strategies used by Sate Blendet traders. The object of this study is the State Blendet trader in Balong, Ponorogo Regency. The method used in this research is descriptive qualitative, is field research, and uses interview techniques. The results of the study concluded that the business constraints of Sate Blendet traders in running a business were when raw materials were scarce, or those commonly used were not available, production was long when raw materials increased, the traders reduced the size of the satay, technological stuttering, less able to develop business, product availability, and service—not keeping clean. In terms of survival strategy, all variables have been fully fulfilled with the theory of business survival strategy. They start from access to raw materials, production, value, promotional capabilities, limited market, business opportunities, product availability, and services. The results of implementing the business strategy on Sate Blendet traders have been successful, starting from access and raw materials used, faster, more efficient production, saving time and energy, from service successfully maintaining consumer loyalty, increasing consumers, and increasing sales. This study contributes to developing the concept of an in-depth study of survival strategies in maintaining the existence of Sate Blendet traders in Balong, Ponorogo Regency.